Divine Providence, Theodicy, Freedom, and the Essence of Time - Appel, Kurt (Concilium, 2023)
This article shows the significance of the thought of divine providence. This idea leads, as Leibniz shows, to a world sufficiently justified in God's love. There is no mechanistic providence in view here; rather, the point is that human freedom always responds to the infinite openness and the associated sense of divine creativity. Leibniz thereby shows the relational content of divine providence, Kant the significance of autonomy and Hegel the solidary being-with, which opens the bodies in their vulnerability towards each other and makes them the place of experiencing God. In all three thinkers, the idea of providence offers potential for resistance against a nihilistic devaluation of the world. The conclusion of the chapter shows that the tense from which the speech of divine providence can make sense is the future anterior.